The possibility of obtaining beta-anhydrite from waste nitrogypsum - Marinković S.; Kostić-Pulek A.; Popov S.; Đinović J.; Trifunović Prvoslav (Journal of Mining and Metallurgy. Section B: Metallurgy)
The possibility of obtaining β - anhydrite from nitrogypsum, which is waste from a nitrocellulose plant, was investigated. It was shown by means of qualitative IR analysis that the product obtained by heating nitrogypsum for 5 hours at 700 o C was â - anhydrite. When the β- anhydrite was mixed with water at a W/S (water/solid) ratio of 0.54 in presence of different accelerators (CaO, mixture CaO - ash, ash, Na2SO4 and K2SO4), pastes were formed which hardened on standing. The compressive strength of the hardened samples was measured after 7 and 28 days and their composition determined by qualitative IR analysis. On the basis of these results, it was observed that a relationship exists between the composition (depending on the used accelerator) and the compression strength of the samples. Namely, the formation of large cores of double salts: syngenite (K2SO4 ⋅CaSO4 ⋅H2O) and glauberite (Na2SO4 ⋅CaSO4), in the presence of the accelerators K2SO4 and Na2SO4, respectively, was due to the rapid and complete crystallization of the dihydrate (CaSO4 ⋅2H2O). This fast crystal growth of the dihydrate resulted in high compressive strengths of these samples. In the other samples (prepared in presence of the accelerators: CaO, mixture CaO - ash and ash), dihydrate did not form and, consequently, their compressive strength was low.